Amendment to Steps to Address Excessive Delays in the Completion of Article IV Consultations or Mandatory Financial Stability Assessments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2013)
In February 2012, the Executive Board adopted new procedures to address excessive delays in the completion of Article IV consultations. These consisted of three formal steps to be applied to all members with serious delays, regardless of the reason for delay, recognizing that the obligation to consult with the Fund under Article IV applies uniformly to all members. These steps are: (i) sending a letter from the Managing Director where an Article IV consultation is delayed for more than 12 months from the expected deadline for its conclusion; (ii) publishing a list of members with Article IV consultations delayed for over 18 months; and (iii) holding an informal session to brief Executive Directors on the economic developments and policies of a member with Article IV consultations delayed for over 18 months. While the implementation of the Decision has been relatively smooth, experience to date has led staff to believe that a modification of the Decision should be considered. In particular, the lack of leeway in the Decision regarding the notification by the Managing Director to a member whose Article IV consultation has been delayed by more than 12 months has proved to be inappropriate in some cases.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Article IV Consultation Discussion; Notification; PP